DISASTER RISK GOVERNANCE AND SOCIO-ECOLOGICAL VULNERABILITY IN THE DEVELOPMENT OF REMPANG ISLAND - Diga Putri Oktaviane; Yustina Yustina (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The development of Rempang Island through the Rempang Eco-City project has become one of Indonesia’s strategic initiatives to promote investment, industrialization, and regional economic growth in coastal areas. While the project is expected to strengthen economic competitiveness and attract large-scale investment, its implementation has generated significant social, environmental, and governance challenges. Existing studies on Rempang have primarily focused on land disputes, relocation issues, and agrarian conflicts, with limited attention given to disaster risk governance and socio-ecological vulnerability perspectives. This study aims to analyze the development of Rempang Island through the lens of Disaster Risk Governance (DRG) and socio-ecological vulnerability to understand how development policies, environmental change, and governance arrangements interact in shaping risks within coastal regions. This study employs a qualitative approach using literature review and policy analysis. Data were collected from government regulations, official reports, public policy documents, human rights reports, academic publications, and other credible secondary sources. The analytical framework integrates disaster risk governance, socio-ecological vulnerability, and public policy theories. The findings indicate that the Rempang conflict should not be understood solely as an agrarian dispute or community resistance to relocation. Instead, it reflects broader governance challenges associated with integrating disaster risk considerations into coastal development policies. The project has the potential to generate socio-ecological vulnerabilities related to land tenure uncertainty, livelihood transformation, cultural identity concerns, environmental pressures, and limited stakeholder participation. The study argues that sustainable coastal development depends not only on economic investment but also on the capacity of governance systems to manage emerging risks through collaborative, adaptive, and inclusive approaches. The article contributes to the literature by positioning the Rempang case as a governance-of-risk issue and highlighting the need to integrate economic development, environmental sustainability, and disaster risk reduction within coastal governance frameworks.